Gene polymorphisms of uric acid are associated with pre-eclampsia in South Africans of African ancestry - Olive P Khaliq; Tadashi Konoshita; Jagidesa Moodely; Veron Ramsuran; Thajasvarie Naicker (Taylor & Francis Group, 2020)
Objectives To investigate the association of uric acid gene polymorphisms and Pre-eclampsia. Methods 637 women of African ancestry [280 controls, 357 pre-eclampsia (early-onset = 187, late-onset = 170]) retrospectively. The rs505802, rs1212986, and rs1014290 SNPs were genotyped from purified DNA using real-time PCR. Results CT genotype (rs505802) was higher in pre-eclampsia [Adjusted p = 0.028*: OR (95% CI) = 1.73 (1.258-2.442)] and late-onset pre-eclampsia [Adjusted p = 0.027*: OR (95% CI) = 1.75 (1.165-2.2628)] than controls. CT genotype (rs1014290) was higher in early-onset pre-eclampsia [Adjusted p-value = 0.040*: OR (95% CI) = 1.60 (1.102-2.325)] than controls. Conclusion The genotyped rs505802 and rs1014290 are significantly associated with pre-eclampsia